Perkembangan Seni Pedalangan dalam Perspektif Perubahan Sosial - Soetarno Soetarno (Institut Seni Indonesia Surakarta, 2008)
This article discusses about the development of puppety recently (2008) which based on an observation, it tends to develop forwards entertaining form as commercial commodities. The problem will be analyzed with Raymon William theory about 3 cultural powers is one historical period. From the analysis, it can be found that pupperty art can influence society and on the contary, pakeliran can be influenced by any changes in society. Nowadays, wayang performance anticipates social changes.Mean while pakeliran also change along with the changer in society. Keyword : development, social culture, wayangÂ